CORPORATE SOCIAL RESPONSIBILITY : DIMENSI DAN PERSPEKTIF DALAM PENELITIAN-PENELITIAN EMPIRIS - R. Ery Wibowo Agung Santosa (Universitas Muhammadiyah Semarang, 2012)
This paper is a literature study that collects evidence of empirical research on CSR program. Studies on the dimensions of the CSR this opens a new understanding of the breadth of the horizon CSR which include dimensions of environmental, social, stakeholder, economic, and vouluntir. But interesting that empirical studies specifically with accounting background science proves that all these dimensions ultimately lead to a motive or conduct economic dimension Keywords : Corporate Social Resposibility (CSR), Economic Dimension